Pengelolaan Retribusi Sampah Di Kelurahan Lolu Utara Kota Palu - Fahdillah; Daswati; Salingkat, Syarif Permana; Djabier, Yan Suprandy (JPS: Journal of Publicness Studies, 2026)
This research aims to determine the Management of Waste Collection fees in lolu Utara Urban Village, Palu City. This research uses a qualitative descriptive method using management theory which consists of aspects of Planning, Organizing, Leading, Controlling. The basis of this research is to use basic qualitative methods, the types of data are primary and secondary data. The data collection technique used research informants totaling 6 informants consisting of heads of divisions, waste levy officers and mandatory levies. Data and material collection was carried out by observation, interviews and documentation. Based on the research results, the management of waste collection fees in Lolu Utara Village, Palu City, is still not optimal. This is evident from the realization of waste collection fee revenues, which has not been able to achieve the predetermined targets, as well as the fact that revenue growth has not shown significant improvement from year to year. These conditions indicate that there are still various obstacles in the process of collecting and managing waste collection fees, particularly in the aspects of planning, implementation, and supervision. Therefore, improvements and optimization of waste collection fee management are needed to ensure that the existing revenue potential can be utilized more effectively, thereby making a greater contribution to increasing the Local Own-Source Revenue (Pendapatan Asli Daerah/PAD) of Palu City.